Application of Expert Systems to Determine I'rob Signs in a Kalimah Using the Forward Chaining Method - Fauzi Asrofi; Sri Lestanti (Universitas Islam Balitar, 2021)
The existence of technology that is increasingly developing the teaching and learning process will be more efficient and maximized, by presenting an effective and fun learning method so that students or students will be more enthusiastic in learning. The Nasyrul Ulum Islamic Boarding School is one of the salafy Islamic boarding schools located in Modangan village, Nglegok District. In the Islamic boarding school environment, students are required to be able to read the yellow book or kitap without harokat. To find out the harokat, students must first understand the knowledge of nahwu so that we need a system that can help easily understand the science of nahwu, especially the signs of I'rob. The results to be obtained from this research are in the form of an expert system application to determine the I'rob sign by applying the Forward Chaining method. This application is expected to help and make it easier for students and application users to determine or understand the signs of I'rob in a sentence. From the results of expert validation testing by testing 51 rules and with 10 case examples, 100% valid data was obtained from experts who were familiar with the knowledge of nahwu chapter ‘alamatil I'rob by paying attention to the adjustment of certain explanations.